Docking analysis of circulating CTX-M variants in multi-drug resistant, beta-lactamase and biofilm-producing E. coli isolated from pet animals and backyard livestock. (September 2022) - Banerjee, Abhiroop; Pal, Surajit; Goswami, Purba; Batabyal, Kunal; Joardar, Siddhartha Narayan; Dey, Samir; Isore, Devi Prasad; Dutta, Tapan Kumar; Bandyopadhyay, Samiran; Samanta, Indranil
Abstract: The generation of antimicrobial-resistant bacteria largely depends on the use of antimicrobials not only in humans but also in pet animals and livestock. The present study was conducted to detect the occurrence of beta-lactamase and biofilm-producing- E.coli in healthy pet and backyard livestock. The study also intended on molecular docking experiments to confirm the nature of the catalytic mechanism in β-lactamase enzymes, encoded by the various blaCTX-M genotypes and phylogenetic analysis to reveal clonal relationship of the animal origin E. coli isolates with human clinical strains. The rectal swabs were collected from healthy dogs (n = 254), cats (n = 108), sheep (n = 119) and goats (n = 143) in India. In total 247 (76.47%) E. coli strains were identified as ESBL producers. The possession of ESBL-producers was significantly more (p < 0.05) in pets than in the backyard livestock. Most of the strains possessed bla CTX-M-15 like clones. E. coli strains possessing bla CTX-M-15.2, bla CTX-M-157, bla CTX-M-181 and bla CTX-M-218 like clones, isolated from pets were not reported earlier. The study detected 56.65% of E. coli strains as moderate or strong biofilm producers possessing biofilm-associated genes ( csgA, rcsA, rpoS, sdiA ). ESBL-producing E. coli showed phenotypical resistance to tetracycline (93.1%), azithromycin (89.8%), ampicillin (84.2%), cefotaxime (80.9%), doxycycline (82.5%), co-trimoxazole (80.9%), ampicillin/cloxacillin (76.9%). The CTX-M variants obtained in this study were modelled by the SWISS-MODEL and verified. Ligand having minimum binding energy, show the highest affinity of β-lactamases for cefotaxime and cefpodoxime. The Gibbs free energy release for all 14 different complex ranges between −6.9 (CTX-M-15.2+cefpodoxime) to −5.3 (CTX-M-218+cefpodoxime) Kcal/mol. Phylogenetic analysis of the animal origin ESBL- E. coli strains revealed a partial clonal relationship with the clinical isolates of local human patients. The present study described the significant presence of biofilm and β-lactamase producing, multi-drug resistant E. coli in pet animals having public health importance. Graphical abstract: Image 1 Highlights: First large-scale monitoring of ESBL/biofilm producing- E. coli in companion/backyard animals in India. Majority of the strains isolated from both companion/household animals possessed bla CTX-M-15 . Canine E. coli possessing bla CTX-M-15.2, bla CTX-M-157, bla CTX-M-181, bla CTX-M-181 and bla CTX-M-218 are not reported earlier. Docking of CTX-M variants revealed the ligands showing highest affinity of β-lactamases for cefotaxime and cefpodoxime. The animal isolates were clonally related to the local human clinical strains.